2020
DOI: 10.1007/s00520-020-05740-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deployment of virtual mind-body interventions during the COVID-19 outbreak: feasibility, acceptability, and implications for future care

Abstract: Introduction COVID-19 increased stress levels while reducing access to mind-body services in patients with cancer. We describe the rapid deployment of remotely delivered mind-body services to people with cancer during COVID-19, rates of participation, and acceptability from patients' perspectives. Methods Eligible participants were patients with cancer age ≥ 18 years enrolled in a single academic cancer center's online patient portal. Interventions included mind-body group therapy sessions in fitness, meditati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 12 publications
2
45
0
3
Order By: Relevance
“…prominent during the pandemic. The potential of these techniques is con rmed both in current practice within the formal health care systems [46] and ongoing research to provide support during the pandemic (e. g. [47]).…”
Section: Discussionmentioning
confidence: 99%
“…prominent during the pandemic. The potential of these techniques is con rmed both in current practice within the formal health care systems [46] and ongoing research to provide support during the pandemic (e. g. [47]).…”
Section: Discussionmentioning
confidence: 99%
“…In response to these concerns, we rapidly implemented a virtual mind-body program through the Integrative Medicine Service (IMS) at a tertiary National Cancer Institute-designated Comprehensive Cancer Center [28]. The program consisted of a series of virtual, synchronous classes offering a variety of rigorously tested mind-body therapies led by an IMS clinical therapist.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mind-body interventions, including yoga, have been rapidly deployed to patients during the pandemic in some centers. 13 However, to our knowledge, only a limited number of studies provide yoga-based breathing with meditation for frontline health workers. 14 Overall, most participants reported that the intervention was worthwhile, that they would participate again, and recommend this pranayama and meditation practice to others.…”
Section: Discussionmentioning
confidence: 99%